The crystal structure of poly[bis(N,N-dimethylformamide-κ1O)-tetrakis(μ2-cyanido-κ2C:N)dinickel(II)], C10H14N6O2Ni2 - Yang Shuang-Hua (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C10H14N6O2Ni2, monoclinic, I2/m (no. 12), a = 6.7377(1) Å, b = 7.3500(1) Å, c = 14.8647(2) Å, β = 96.051(1)°, V = 732.030(18) Å3, Z = 8, Rgt(F) = 0.0314, wRref(F2) = 0.0996, T = 150.01(10) K.